Impairments to the multisensory integration brain regions during migraine chronification: correlation with the vestibular dysfunction - Dong, Liang; Fan, Xiaoping; Fan, Yulan; Li, Ximao; Li, Hui; Zhou, Jiying (Frontiers in Molecular Neuroscience, 2023)
Abstract Objectives: Migraine is often combined with vestibular dysfunction, particularly in patients with chronic migraine (CM). However, the pathogenesis of migraine chronification leading to vestibular dysfunction is not fully understood. The current study investigated whether structural or functional impairments to the brain during migraine chronification could be associated with vestibular dysfunction development. Methods: The eligible participants underwent clinical assessment and MRI scans. Voxel-based morphometry (VBM) determined structural impairment by evaluating alterations in gray matter volume (GMV). Functional impairment was assessed by the mean amplitude of low-frequency fluctuation (mALFF). Furthermore, the resting-state functional connectivity (rsFC) of regions possessing impairment was examined with a seed-based approach. We also analyzed the correlations between altered neuroimaging features with clinical variables and performed multiple linear regression. Results: Eighteen CM patients, 18 episodic migraine (EM) patients, and 18 healthy controls (HC) were included in this study. A one-way ANOVA indicated the group differences in mALFF. These were located within right supramarginal gyrus (SMG), left angular gyrus (AG), middle frontal gyrus (MFG), left middle occipital gyrus (MOG), right rolandic operculum (Rol) and left superior parietal gyrus (SPG). During rsFC analysis, the CM group had more enhanced rsFC of left SPG with left MOG than the EM and HC groups. The EM group revealed enhanced rsFC of left SPG with left AG than the CM and HC groups. In multiple linear regression, after controlling for age, BMI and disease duration, the rsFC of left SPG with left MOG (β= 48.896, p= 0.021) was found to predict the total Dizziness Handicap Inventory (DHI) score with an explained variance of 25.1%. Moreover, the rsFC of left SPG with left MOG (β= 1.253, p= 0.003) and right SMG (β= -1.571, p= 0.049) were significant predictors of migraine frequency, accounting for a total explained variance of 73.8%. Conclusion: The functional impairments due to migraine chronification are primarily concentrated in the multisensory integration-related brain regions. Additionally, the rsFC of SPG with MOG can predict the frequency of migraine and the degree of vestibular dysfunction. Therefore, these neuroimaging features could be potential mechanisms and therapeutic targets for developing vestibular dysfunction in migraine.